ASPEK HUKUM PENGGUNAAN SENJATA OLEH BRIMOB DALAM MENANGANI GANGGUAN KEAMANAN DI PAPUA BARAT - Yakobus Frendi Weriditi (Fakultas Hukum, Universitas Caritas Indonesia, 2026)
The use of firearms by Mobile Brigade (Brimob) personnel falls within the scope of state authority to maintain public security and order. However, the use of lethal force frequently sparks debates regarding law and human rights, particularly when addressing security disturbances in West Papua, a region characterized by complex conflict dynamics and threat levels. Various reports alleging the use of excessive force highlight the need to examine the legal basis, the application of the proportionality principle, and the accountability mechanisms governing the use of firearms by police personnel. This study aims to analyze the legal basis for the use of weapons by Brimob in handling security disturbances in West Papua, examine the application of the proportionality principle regarding firearm use, and investigate the forms of accountability and legal implications arising from violations involving the use of firearms by police personnel. The study employs a normative-juridical legal research method, utilizing statutory, conceptual, and case-based approaches. Legal materials were gathered through a literature review comprising legislation, legal doctrine, court rulings, scholarly literature, and international legal instruments concerning the use of force by law enforcement officials. Analysis was conducted qualitatively through legal interpretation and deductive reasoning. The findings indicate that the use of firearms by Brimob rests on a solid legal foundation within both national and international legal systems. Nevertheless, the use of firearms must consistently adhere to the principles of legality, necessity, proportionality, and accountability. Violations of these principles can lead to criminal, administrative, and civil consequences, as well as social repercussions that undermine public trust in the police institution. Consequently, strengthening oversight mechanisms, enhancing personnel professionalism, and upholding human rights are essential prerequisites for the use of force by Brimob.